Holistic Primary Care–Based Management of Typhoid Fever in a Toddler from a Resource-Limited Community Setting - Zaleha Ulfa; Putri Nabila Febrianti; Putri Novita Sari; Rahmawati Sari; Ratna Gumilang Sari; Rahmi Rahmawati; Manmeet Kaur; Alok Shukla (CV. FOUNDAE, 2026)
Typhoid fever remains a significant public health challenge in many low- and middle-income countries, including Indonesia, where inadequate sanitation, limited access to clean water, and suboptimal hygiene practices continue to facilitate disease transmission. Although typhoid fever is more commonly reported in school-aged children and adolescents, its occurrence in toddlers poses unique diagnostic and management challenges due to atypical clinical presentations and increased vulnerability to dehydration and complications. Early recognition and comprehensive management at the primary health care level are therefore critical. This study describes the holistic primary care–based management of typhoid fever in a 14-month-old boy presenting to a community health center in Bandar Lampung, Indonesia. The patient was brought with a three-day history of persistent fever and a one-week history of watery diarrhea, accompanied by decreased appetite, irritability, and generalized weakness. A holistic diagnostic approach integrating clinical symptoms, physical examination, environmental exposure, and family hygiene practices was applied. Key clinical features included a fever pattern worsening in the late afternoon to evening, prolonged diarrhea, and a coated tongue with erythematous margins, strongly suggestive of typhoid fever in the absence of other focal infections. Management combined pharmacological and non-pharmacological interventions tailored to the toddler age group and primary care setting. Pharmacological therapy consisted of first-line antibiotic treatment with cotrimoxazole, antipyretic therapy, zinc supplementation, and oral rehydration therapy to prevent dehydration. Non-pharmacological interventions emphasized continued breastfeeding, adequate fluid intake, safe food preparation, access to clean drinking water, and strict hand hygiene practices within the household. Family members were actively involved in the care process to ensure adherence to treatment and implementation of preventive measures. Clinical improvement was observed following the integrated intervention, with resolution of fever and gastrointestinal symptoms and restoration of appetite and activity levels. This approach highlights the importance of combining clinical management with family-centered hygiene education and environmental risk assessment. The findings underscore the critical role of primary health care services in early detection, effective treatment, and prevention of typhoid fever among vulnerable pediatric populations.